The responsibility to prevent: overcoming the challenges of atrocity prevention - Sharma, Serena K.; Welsh, Jennifer (Oxford University Press, 2015)
Examines ways to operationalize the responsibility to prevent genocide, crimes against humanity, war crimes, and ethnic cleansing. Develops a strategic framework to identify the appropriate scope and substance of preventive dimensions and the tools that can be used to prevent escalation such as sanctions, mediation, international criminal justice, and military intervention